ANTIPROTOZOAL ACTIVITY OF EXTRACTS OF ELAEODENDRON TRICHOTOMUM (CELASTRACEAE) - Roca-Mézquita, Carolina; Graniel-Sabido, Manlio; Moo-Puc, Rosa E.; Leon-Déniz, Lorena V.; Gamboa-León, RubÃ; Arjona-Ruiz, Carely; Tun-Garrido, Juan; Mirón-López, Gumersindo; Mena-Rejon, Gonzalo J. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Chagas disease, amebiasis, giardiasis and trichomoniasis represent a serious health problem in Latin America. The drugsemployed to treat these illnesses produce important side effects and resistant strains have appeared. The present study was aimed toevaluate the antiprotozoal activity of leaves, stem bark and root bark of Elaeodendron trichotomum, a celastraceus, that is used in Mexicoas an anti-infective in febrile-type diseases.Materials and methods: Dichloromethane and methanol extracts of leaves, bark and roots of Elaeodendron trichotomum were testedagainst Entamoeba histolytica, Giardia lamblia, Trichomonas vaginalis, and Trypanosoma cruzi. A quantitative HPLC analysis ofpristimerin and tingenone was performed.Results: The dichloromethane extract of roots was active against E. histolytica, G. lamblia, T. vaginalis, and T. cruzi, at IC50’s of 0.80,0.44, 0.46, and 2.68 μg/mL, respectively. The HPLC analysis revealed the presence of tingenone (3.84%) and pristimerin (0.14%).Conclusions: The dichloromethane extract of the roots bark showed significant activity against all screened protozoa.